Gambaran Kadar Hemoglobin (Hb) pada Ibu Hamil dengan Menggunakan Alat Hematologi Analyzer di Puskesmas Lubuk Basung - Fitri, Afifah Ismu; Achyar, Afifatul; Yuniarti, Elsa (MASALIQ, 2024)
Hematological changes in pregnant women are a response to multifactorial hormonal changes, one of the hematological changes that occur is caused by anemia. Anemia in pregnant women is physiological that can occur in normal pregnancy. Some factors that can be experienced by pregnant women to experience anemia are nutritional knowledge factors, age factors that are too young or too old, and health in the nutritional consumption patterns of pregnant women. The purpose of this study was to see a description of hemoglobin (hb) levels in pregnant women using a hematology analyzer at the Lubuk Basung health center. The implementation of activities carried out at the Lubuk Basung Health Center Health Service Laboratory, Agam Regency, West Sumatra Province by performing venous blood collection procedures and then performing hemoglobin level examination procedures using a hematology analyzer. the conclusions obtained are the results of research conducted on 69 samples in June-July 2023 on the description of hemoglobin levels in pregnant women at the Lubuk Basung Health Center, it was concluded that of the 69 samples there were pregnant women with an age range of 20-35 years totaling 62 people (89.9%), and age> 35 years totaling 7 people (10.1%). This shows that pregnant women who do Hb checks at the Lubuk Basung Health Center tend to be productive age, and of the 69 samples, low Hb levels (<11 gr/dl) were 17 people (24.6%) and normal Hb levels (11-15 gr/dl) were 52 people (75.4%).